Ben Yokoyama and the cookie of doom - Swanson, Matthew, 1974- (Swanson, Matthew, 1974- Cookie chronicles., 2021)
Eight-year-old Ben takes a fortune cookie literally, and believing he has only one day left to live, tries to do everything he has always wanted to before nightfall.